Gendered use of hedges in the discussion and conclusion sections of research articles - Lamya Alhuqbani; Mohammed Alhuqbani (Russian Journal of Linguistics, 2025)
Following Lakoff’s (1975) claim that women hedge in speech more often than men, a large number of studies have investigated the role of gender in academic discourse and produced limited evidence, indicating the need for more research to highlight the role of gender in academic writing. The aim of this study was to cross-culturally examine how gender may affect the use of hedges in the discussion and conclusion sections of research articles. For this purpose, the study adopted Salager-Meyer’s (1997) taxonomy of hedges to qualitatively and quantitatively examine the types, frequency and gendered use of hedges in a small-scale corpus of research articles produced by 20 Saudi male and female researchers. The overall results showed that both genders employed Salager-Meyer’s taxonomy of hedges and used more hedges in the discussion than in the conclusion . Males hedged more than females, but the difference was not statistically significant except in certain cases, such as the use of two modal lexical verbs ( indicate and seem ) and the modal auxiliary verb ( must ). Moreover, the results revealed a marginal significant difference in the use of adjectival , adverbial and nominal phrases. Females tended to employ more of these hedges than their male counterparts. The findings contribute to a better understanding of the relationship between gender and hedging in academic discourse, and may guide postgraduate students towards the appropriate use of hedging devices in their research development. They also emphasize the need for further research on the role of gender across disciplines, languages and cultures.